The architecture of financial networks and models of financial instruments according to the "just transition mechanism" at the European level - Otilia Manta; Kōstas Iō. Guliamos; Jie Kong; Zhou Li; Nguyen Minh Ha; R. P. Mohanty; Hongmei Yang; Ruihui Pu; Xiao-Guang Yue (Journal of Risk and Financial Management, 2020)
At the global level and in particular the European level, challenges related to climate change and the transition to green transactions have created an imperative where identifying or developing innovative financial instruments, appropriate for these priorities, have become our research priorities and objectives. Starting from the analysis of the European Investment Plan for green transactions, as well as the EU Directive 2018/410 of the European Parliament and of the Council, in conjunction with ongoing efforts to identify innovative financing tools, research is presented based on hypotheses using concepts and models of green financing. The paper aims to analyze the main concepts and phenomena that could be considered generative factors for current financial market trends, as well as the inventory of facts and acts that provide a picture of the financial market. Based on these investigations, this paper suggest how we can best analyze the economic environment, processes, and resources in terms of their predictions regarding the sustainability of financial markets in the context of current challenges. Moreover, our paper aims to highlight in our empirical research the above-mentioned aspects, including the analysis of the emergence of new financial instruments at the global level with a direct impact on financial sustainability at the European level, including reflecting certain particularities of financial markets Romania. This research will be both a scientific contribution to the specialized literature and a possible support tool for the practical activities of entrepreneurs in their economic endeavor of developing sustainable businesses.
Keywords: 330; climate change; financial instruments; green transactions; sustainable development